PEMBEBANAN NAFKAH IDDAH DAN MUT’AH DALAM PERKARA CERAI GUGAT DALAM TINJAUAN HUKUM ISLAM DI INDONESIA DAN MALAYSIA - Rizki Putra Pratama; Zuraidah Azkia; A'dawiyah Bt Ismail (Usroh: Jurnal Hukum Keluarga Islam, 2023)
Abstract Divorce lawsuits filed by wives are often not accompanied by additional demands on the husband to provide Iddah and mutah. Because many cases that occur in a divorce lawsuit, a wife does not get the right to provide iddah and mut'ah. Even though the application for a living right can be submitted at the time of filing a divorce suit as in the Decision of the Pangkalan Balai Religious Court No.727/Pdt.G/2021/Pa.Pkb. The purpose of this paper is to find out the legal basis that the judge considers regarding the imposition of iddah and mut'ah maintenance in divorce cases and to understand the review of Islamic law in Indonesia and Malaysia on the imposition of iddah and mut'ah maintenance in divorce cases. This research uses a type of field research or what is called (field research). From the results of the study it was found that the judge made a decision based on the consideration of the party's evidence presented at trial, where evidence was found that the plaintiff was not nusyuz so that based on the theory of justice and the protection of women's rights, the judge could make a decision in accordance with the ijtihad that was carried out. In addition, according to Islamic law in Indonesia it is in line with Article 41 of Law No. 1 of 1974. Meanwhile, according to Islamic law in Malaysia it is in line with the Anakmen Islamic Family Law Number 17 of 2003. Keywords.: Divorce; Iddah income; Mut'ah